ENHANCED QR CODE BASED DIGITAL SIGNATURES FOR SECURE DOCUMENT MANAGEMENT TOWARD SUSTAINABLE GREEN INVESTMENT - Bagas Dwi Yulianto; Wisnu Wendanto (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2026)
This study proposes a secure QR Code–based digital signature framework to support paperless legal document management and sustainable green investment. The method integrates SHA-256 hashing and enhanced Multi-Factor RSA encryption, combined with a block-based hexadecimal processing approach to improve computational efficiency while maintaining strong cryptographic security. The generated encrypted signature is embedded into a QR Code, enabling real-time document verification through decryption and hash comparison. The main contribution of this study lies in the integration of optimized Multi-Factor RSA with QR-based authentication, providing both high security and practical verification capability within a unified system. Experimental results demonstrate successful authentication across all test cases, with robust performance under image distortions such as rotation, sharpening, Poisson noise, and Gaussian noise. The proposed method achieves an average Avalanche Effect of 85.78%, indicating strong diffusion and resistance to cryptographic attacks. Furthermore, a sustainability assessment involving 100 authorized respondents from education, corporate, and government sectors produced average scores above 4.0 across green computing, legal reliability, technology adoption, and digital security dimensions. These findings confirm that the proposed framework enhances digital document security while supporting environmentally sustainable and legally compliant paperless transformation.